Hierarchical modelling of small-scale irrigation: Constraints and opportunities for adoption in sub-Saharan Africa - Haile, Beliyou; Mekonnen, Dawit Kelemework; Choufani, Jowel; Ringler, Claudia; Bryan, Elizabeth (World Scientific Publishing, 2022)
Irrigation has significant potential to enhance productivity, resilience to climatic risks and nutrition security in Sub-Saharan Africa. While the focus has historically been on large-scale dam-based schemes, farmer-managed small-scale irrigation (SSI) has gained increased attention in recent years. Using data from Ethiopia, Tanzania and Ghana, we first examine patterns of adoption of different SSI technologies. Next, we employ hierarchical modelling to examine which variables are associated with observed adoption patterns and cluster effects that explain variation in irrigation adoption. We document significant cross-country variation in adoption patterns and find a positive association between plot-level use of SSI and the intensity of agricultural labor and inorganic fertilizers applied on the plot. Community-level intra-cluster correlation (ICC) is the highest in Tanzania, where gravity-fed irrigation is most common while farm-level ICC is the highest in Ethiopia where motorized technologies are more common. These results suggest the need for localized investments to ease locale-specific potential constraints. For example, easing possible liquidity constraints to acquiring motorized technologies can be more effective in Ethiopia while the construction of dams and improved conveyance systems, as well as the strengthening of community-based irrigation management (e.g., through Water User Associations (WUAs)) can be more effective in Tanzania. Further research is needed to understand pathways for selected plot-level characteristics that affect use of SSI including status of plot ownership and the gender of the plot manager.